Constructivist Grounded Theory or Interpretive Phenomenology? Methodological Choices Within Specific Study Contexts. (7th February 2022) - Burns, Margie; Bally, Jill; Burles, Meridith; Holtslander, Lorraine; Peacock, Shelley
Constructivist research methodologies are useful in discerning meanings of experience to subsequently inform and improve healthcare practice. For researchers who philosophically align with the constructivist paradigm, numerous methodologies are available from which to choose to address research questions. However, it can be challenging for researchers, especially novice ones, to choose the most appropriate methodology that aligns with the current state of knowledge of the identified topic, proposed research question, and the study purpose. To reduce the confusion faced by health researchers when choosing an appropriate methodology for a specific study, this paper compares two popular qualitative health research approaches: constructivist grounded theory and interpretive phenomenology. Philosophical underpinnings and the epistemological and ontological evolution of each methodology are explored with similarities and differences highlighted. Manifestation of the philosophical foundations of constructivist grounded theory and interpretive phenomenology are described in relation to data collection, analysis, and the research findings. To illustrate distinctions of each approach and support researchers in the navigation of methodological decision-making, a specific healthcare study context is presented: the rural family members' experiences of a relative's interhospital transfer for advanced critical care services. This study context is increasingly being recognized as an important area of healthcare research and practice. However, gaps in knowledge persist, specifically in relation to the experiences of rural family members when a critically ill relative requires an interhospital transfer to a distant urban center for advanced critical care services. Improved understanding of such experiences is necessary to inform the care provided to rural family members, potentially mitigating short and long-term negative consequences for these individuals. Within this example, the importance of the research purpose and research question within a specific study context is underscored as central to appropriate methodological decision-making.